Excess of de novo variants in genes involved in chromatin remodelling in patients with marfanoid habitus and intellectual disability. Issue 7 (10th April 2020) - Chevarin, Martin; Duffourd, Yannis; A. Barnard, Rebecca; Moutton, Sébastien; Lecoquierre, François; Daoud, Fatma; Kuentz, Paul; Cabret, Caroline; Thevenon, Julien; Gautier, Elodie; Callier, Patrick; St-Onge, Judith; et al.
Abstract : Purpose: Marfanoid habitus (MH) combined with intellectual disability (ID) (MHID) is a clinically and genetically heterogeneous presentation. The combination of array CGH and targeted sequencing of genes responsible for Marfan or Lujan–Fryns syndrome explain no more than 20% of subjects. Methods: To further decipher the genetic basis of MHID, we performed exome sequencing on a combination of trio-based (33 subjects) or single probands (31 subjects), of which 61 were sporadic. Results: We identified eight genes with de novo variants (DNVs) in at least two unrelated individuals ( ARID1B, ATP1A1, DLG4, EHMT1, NFIX, NSD1, NUP205 and ZEB2 ). Using simulation models, we showed that five genes ( DLG4, NFIX, EHMT1, ZEB2 and ATP1A1 ) met conservative Bonferroni genomewide significance for an excess of the observed de novo point variants. Overall, at least one pathogenic or likely pathogenic variant was identified in 54.7% of subjects (35/64). These variants fell within 27 genes previously associated with Mendelian disorders, including NSD1 and NFIX, which are known to be mutated in overgrowth syndromes. Conclusion: We demonstrated that DNVs were enriched in chromatin remodelling (p=2×10 −4 ) and genes regulated by the fragile X mental retardation protein (p=3×10 −8 ), highlighting overlapping genetic mechanisms between MHID and related neurodevelopmental disorders.